Mucosal administration of a live attenuated recombinant COVID-19 vaccine protects nonhuman primates from SARS-CoV-2 - Tioni, Mariana F.; Jordan, Robert; Pena, Angie Silva; Garg, Aditya; Wu, Danlu; Phan, Shannon I.; Weiss, Christopher M.; Cheng, Xing; Greenhouse, Jack; Orekov, Tatyana; Valentin, Daniel; Kar, Swagata; et al. (npj vaccines, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of the COVID-19 global pandemic. SARS-CoV-2 is an enveloped RNA virus that relies on its trimeric surface glycoprotein spike for entry into host cells. Here we describe the COVID-19 vaccine candidate MV-014-212, a live, attenuated, recombinant human respiratory syncytial virus expressing a chimeric SARS-CoV-2 spike as the only viral envelope protein. MV-014-212 was attenuated and immunogenic in African green monkeys (AGMs). One mucosal administration of MV-014-212 in AGMs protected against SARS-CoV-2 challenge, reducing by more than 200-fold the peak shedding of SARS-CoV-2 in the nose. MV-014-212 elicited mucosal immunoglobulin A in the nose and neutralizing antibodies in serum that exhibited cross-neutralization against virus variants of concern Alpha, Beta, and Delta. Intranasally delivered, live attenuated vaccines such as MV-014-212 entail low-cost manufacturing suitable for global deployment. MV-014-212 is currently in Phase 1 clinical trials as an intranasal COVID-19 vaccine.